Carbapenem-resistant Enterobacteriaceae Infections in Children: An Italian Retrospective Multicenter Study. Issue 8 (August 2016) - Montagnani, Carlotta; Prato, Manuela; Scolfaro, Carlo; Colombo, Sara; Esposito, Susanna; Tagliabue, Claudia; Lo Vecchio, Andrea; Bruzzese, Eugenia; Loy, Anna; Cursi, Laura; Vuerich, Marco; de Martino, Maurizio; et al.
Abstract : Background: The spread of carbapenem-resistant Enterobacteriaceae (CRE) is a health problem of major concern. CRE-related infections have significant morbidity and mortality, but data on CRE infection in pediatric population are limited. The aim of this study was to analyze epidemiologic and clinical characteristics, risk factors, therapeutic options and outcome of CRE infections in children in Italy. Methods: We performed a retrospective, multicenter, observational study of children with confirmed CRE infection or colonization admitted between January 1, 2011, and March 1, 2014, to 7 Italian pediatric centers. Results: Sixty-nine patients presenting 74 CRE infections and/or colonization were included. The most frequently isolated strain was Klebsiella pneumoniae carbapenemase -producing K. pneumoniae. Children with CRE infections had longer length of stay in hospital ( P < 0.001), duration of disease ( P = 0.001) and antimicrobial treatment ( P < 0.001) than colonized children. Oncologic/immunosuppressive conditions are one of the factors significantly associated with a fatal outcome among children with CRE infections. Conclusions: Our study confirms that CRE infections affect mostly children with oncologic diseases and immunosuppression. Controlled studies in large cohorts are needed to evaluate the best therapeutic options and to assess further risk factors influencing outcomes and the survival of pediatric patients with infections caused by CRE.